Analysis of the volatile oils from three species of the gender Syzygium (Research, Society and Development, 2021)
The species Syzygium cumini, Syzygium malaccense and Syzygium jambos, belong to the family Myrtaceae and are popularly known, respectively, by jambolan, red jambo and yellow jambo. These species are used in traditional medicine to treat diabetes mellitus, asthma, bronchitis, diuresis, gastrointestinal and respiratory infections, properties antipyretic, anti-inflammatory, antirheumatic and several other uses. The objective of this work is to identify and quantify the volatile compounds in the leaves of S. cumini, S. malaccense and S. jambos. The volatile oils were obtained by hydrodistillation using Clevenger apparatus and analyzed by Gas Chromatography Coupled to Mass Spectrometry (GC-MS). It was possible to identify 44 compounds present in the volatile oils of the leaves, being 20 compounds of S. cumini, 9 compounds of S. malaccense and 15 compounds of S. jambos. The major compounds present in the species S. cumini were α-terpineol, β-caryophyllene and α-humulene; for the species S. malaccense were aristolochene, γ-himachalene and δ-amorphene; and for S. jambos species were β-cariophyllene, (E,E)-α-farnesene and cariophyllene alcohol. The species S. cumini, S. malaccense and S. jambos showed considerable differences in terms of volatile compounds, it is important to know their constituents in order to promote further studies focused on their medicinal potential.